2004
DOI: 10.1029/2003tc001576
|View full text |Cite
|
Sign up to set email alerts
|

Folding and inversion tectonics in the Anti‐Atlas of Morocco

Abstract: The late Variscan Anti‐Atlas of Morocco shows some conspicuous deviations from the standard anatomy of foreland fold‐and‐thrust belts. Large basement inliers crop out at a very short distance of less than 50 km behind the southeastern front of the fold belt, reminiscent of Windriver‐style basement uplifts. In contrast to the Rocky Mountain foreland, however, the Anti‐Atlas basement uplifts punctuate tightly folded Paleozoic cover series similar in tectonic style to the Appalachian Valley and Ridge province. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…The epigenetic view is supported when the copper sulphide mineralization displays an intense structural control indicating that mineralization took place contemporaneously with basin inversion and orogeny. The Anti-Atlas Belt in Morocco comprises large Proterozoic basement inliers consolidated during the Eburnean and the Pan-African orogeny [11] and a Late Ediacaran to Paleozoic sedimentary cover weakly folded during the Hercynian orogeny [12,13]. The terminal Neoproterozoic to Lower Cambrian cover includes important copper orebodies ( Figure 1), with up to 200 occurrences [14], some of which are currently mined.…”
Section: Introductionmentioning
confidence: 99%
“…The epigenetic view is supported when the copper sulphide mineralization displays an intense structural control indicating that mineralization took place contemporaneously with basin inversion and orogeny. The Anti-Atlas Belt in Morocco comprises large Proterozoic basement inliers consolidated during the Eburnean and the Pan-African orogeny [11] and a Late Ediacaran to Paleozoic sedimentary cover weakly folded during the Hercynian orogeny [12,13]. The terminal Neoproterozoic to Lower Cambrian cover includes important copper orebodies ( Figure 1), with up to 200 occurrences [14], some of which are currently mined.…”
Section: Introductionmentioning
confidence: 99%
“…the shortening in the western part of the AA lies between 15% and 25% (Helg et al 2004;burkhard et al 2006). No large-scale thrusting or duplexing is known.…”
Section: Geological Settingmentioning
confidence: 99%
“…the Variscan shortening in the western Anti-Atlas varies between 15 and 25% (caritg et al 2003;Helg et al 2004;burkhard et al 2006;robert-charrue & burkhard this volume). In a very simple model assuming constant cross section area, the tectonic thickening would be roughly of the same magnitude, i.e.…”
Section: Tectonic Thickening and Thermal Eventsmentioning
confidence: 99%
“…The white sinuous band against a fold ridge is a dry stream. Recently, Helg et al (2004) showed that the Anti Atlas of Morocco is a special type of foreland fold belt lacking any evidence for thrust faults other than the occasional steep reverse fault found near basement inliers. (Courtesy: NASA and Earth Satellite Corporation.)…”
Section: Structural Mappingmentioning
confidence: 99%